Comparison of spontaneous ascites filtration and reinfusion with total paracentesis with intravenous albumin infusion in cirrhotic patients with tense ascites. Issue 6843 (27th June 1992) - Bruno, S.; Borzio, M.; Romagnoni, M.; Battezzati, P. M.; Rossi, S.; Chiesa, A.; Podda, M.
Abstract : OBJECTIVE–To compare the effectiveness and safety of spontaneous ascites filtration and reinfusion and total paracentesis plus intravenous albumin infusion in cirrhotic patients with tense ascites. DESIGN–Randomised trial of the two treatments. SETTING–Teaching hospital and district general hospital in Milan. PATIENTS–45 consecutive cirrhotic patients with recurrent tense ascites and urinary sodium excretion rate less than 20 mmol/day. 35 fulfilled admission criteria and completed the study. 17 received spontaneous ascites filtration and 18 paracentesis plus albumin infusion. MAIN OUTCOME MEASURES–Body weight; urinary volume; serum and urinary electrolyte, serum fibrinogen, and plasma aldosterone concentrations; and plasma renin activity before the procedure and 24 hours and eight days afterwards. RESULTS–Both procedures were effective in all patients. Weight decreased in both groups and showed no substantial increase after eight days. In patients receiving ascites filtration, values decreased significantly (p less than 0.01) after 24 hours for platelet count (mean relative change 0.92; 99% confidence interval 0.86 to 0.98) and serum fibrinogen concentration (0.92; 0.88 to 0.98) but returned to pretreatment values after eight days; no laboratory and clinical signs of disseminated intravascular coagulation were noted. Three patients in this group had fever, which receded spontaneously. One patient in each group had dilutional hyponatraemia. CONCLUSIONS–Spontaneous ascites filtration and reinfusion is an effective treatment for tense ascites. Reinfusion of the patient's concentrated proteins provides savings without compromising safety.